Content, Production, and Audience Research in Trans TV Program "Islam Itu Indah" - Monarshi, Evri Rizqi; Saraka, Muh. Yahya; Bakti, Andi Faisal; Praptiningsih, Novi Andayani; Hermansah, Tantan (Communicare : Journal of Communication Studies, 2024)
This research aims to describe and construct the research conducted on Trans TV's "Islam Itu Indah" program, which has faced reprimands for violating child protection rules. The study focuses on three forms: 1) stages of content research, 2) production research, and 3) audience research. The "Islam Itu Indah" creative team performs these research types before airing, analyzing findings to ensure compliance and quality. Using Branston and Stafford's theory, the research includes content (internet search), production (pre, production, post), and audience analysis. The study highlights the significance of continuous content research to maintain the program's relevance and quality. It emphasizes the importance of production research in adapting to technological advancements and audience research for understanding the morning audience's characteristics. The findings illustrate the necessity of aligning content, production, and audience strategies to manage a successful daily television program.